'What would happen if you can't see your money?': Visibility and the emergent infrastructures of digital money storage in China. (April 2021) - McDonald, Tom; Guo, Yanan
This article adopts an infrastructural perspective to analyse Chinese migrant factory workers' conceptions of and approaches towards storing money on digital payment platforms. Scholars studying infrastructural systems have emphasised that such systems generally only become visible upon breakdown. However, this article finds that during the emergence of new infrastructures for monetary storage, existing infrastructures – along with the money stored within them – also become rendered conspicuous to users. In such moments, migrant factory workers are forced to assess the differences between existing and new infrastructural systems and make careful decisions over how to store their money. We claim it is necessary to acknowledge the shifting visibility of infrastructures during occasions of systemic transformation. Doing so can help to better understand how users navigate such infrastructures in attempts to solve problems of storage, while in the process re-evaluating their relationships with a variety of entities and institutions.